Adaptation of Blue Ocean Strategy in Increasing Business Markets - Intan Sakinah; Zainab Zahro; Adilla Andinia (Journal of Economics Business Industry, 2023)
Products produced by the XYZ Photography & Video Studio business include photo studio services, graduation studio photos, family studio photos, pre-wedding photos, wedding photos, wedding videos, photo printing, and photo accessories sales. The following problems: Lack of promotion carried out by the management either manually or online, No company targets monthly and yearly, Incomplete brochures and price lists for each product. This study aims to increase revenue and propose strategies to create innovations to stay away from competitors. The methods used are the SWOT and Blue Ocean Strategy (BOS). The SWOT method determines strengths, weaknesses, threats and opportunities. The BOS method is a method used to stay away from competitors. Research conclusion The Company's position in market competition through the SWOT matrix of EFAS and IFAS is in quadrant IV, which means that the Company in this position is very unfavourable because it faces threats and weaknesses from the company. The company has many weaknesses and also faces threats. This position proves that the company's performance is weak and faces major challenges. The company focuses on minimizing internal problems to seize existing market opportunities